Conceptual analysis of Physiology of vision in Ayurveda - Balakrishnan, Praveen (Medknow Publications & Media Pvt Ltd, 2014)
The process by which the world outside is seen is termed as visual process or physiology of vision. There are three phases in this visual process: phase of refraction of light, phase of conversion of light energy into electrical impulse and finally peripheral and central neurophysiology. With the advent of modern instruments step by step biochemical changes occurring at each level of the visual process has been deciphered. Many investigations have emerged to track these changes and helping to diagnose the exact nature of the disease. Ayurveda has described this physiology of vision based on the functions of vata and pitta. Philosophical textbook of ayurveda, Tarka Sangraha, gives certain basics facts of visual process. This article discusses the second and third phase of visual process. Step by step analysis of the visual process through the spectacles of ayurveda amalgamated with the basics of philosophy from Tarka Sangraha has been analyzed critically to generate a concrete idea regarding the physiology and hence thereby interpret the pathology on the grounds of ayurveda based on the investigative reports.